Ottomans, Venetians and Habsburgs: 'Triplex Confinium&#39 - Roksandić, Drago (Array, 2002)
The text is a chapter in a three-volume synthesis of the Turkish history, focusing upon the Ottoman-Habsburg-Venetian triple borderland in Croatian in the Early Modern Period.